1981
DOI: 10.1007/bf00263725
|View full text |Cite
|
Sign up to set email alerts
|

Inheritance of resistance to Okra yellow vein mosaic disease in interspecific crosses of Abelmoschus

Abstract: Two Abelmoschus species, viz., A. manihot (L.) Medik and A. manihot (L.) Medik ssp. manihot, resistant to Okra yellow vein mosaic (YVM) were crossed to A. esculentus cv. 'Pusa Sawani', a susceptible culture. The hybrids were resistant and partially fertile. Segregation pattern for disease reaction in F2, BC1 and subsequent generations of the two crosses revealed that resistance to YVM is controlled by a single dominant gene in each species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 0 publications
2
11
0
Order By: Relevance
“…Among numerous obstacles to a successful seed set, the most significant feature observed was the presence of a physical barrier of multiple tissues between the male (pollen) and female (pistil) gametophytes leading to a low seed and fruit set in Abelmoschus crosses involving the wild relatives. Earlier studies reported that the hybridisation between A. esculentus and its wild species resulted in a low fruit and seed set along with sterile and shrivelled seeds (Ustinova, 1949;Pal et al, 1952;Jambhale & Nerkar, 1981). In the present study, field data substantiated with comparative pollenpistil interaction studies were conducted at various intervals by means of fluorescence microscopy and SEM.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Among numerous obstacles to a successful seed set, the most significant feature observed was the presence of a physical barrier of multiple tissues between the male (pollen) and female (pistil) gametophytes leading to a low seed and fruit set in Abelmoschus crosses involving the wild relatives. Earlier studies reported that the hybridisation between A. esculentus and its wild species resulted in a low fruit and seed set along with sterile and shrivelled seeds (Ustinova, 1949;Pal et al, 1952;Jambhale & Nerkar, 1981). In the present study, field data substantiated with comparative pollenpistil interaction studies were conducted at various intervals by means of fluorescence microscopy and SEM.…”
Section: Discussionmentioning
confidence: 53%
“…Earlier studies and efforts to bring useful genes from wild okra were only partially successful due to presence of unidentified pre-and post-fertilisation barriers to gene flow in this genus (Pal et al, 1952;Kuwada, 1957Kuwada, , 1966Siemonsma, 1982). However, there are highly sporadic attempts aimed at interspecific hybridisations among A. esculentus and its wild relatives so far (Jambhale & Nerkar, 1981;Nerkar, 1991;Tyagi, 2002).…”
mentioning
confidence: 99%
“…many reports showed that YVMD resistance is controlled by two dominant complementary genes (Sharma and Sharma 1984a), on other hand many showed that there is a single dominant gene (Jambhale and Nerkar 1981) or two recessive genes (Singh et al, 1962) responsible governing the resistance against to YVMD. Dhankhar et al, (2005) concluded the hypothesis that two complementary dominant genes were involved in governing the resistance to yellow vein mosaic virus disease in okra.…”
Section: Genetics Of Resistancementioning
confidence: 99%
“…Among these viruses, YVMV transmitted by whiteflies, is the most pressing plant protection problem universally faced by all okra growers [40] [41] causes significant losses in the okra production. Some attempts had been made by several workers to reduce to disease through the vector control [42]- [45] and also through the breeding strategies [46] [47]. Resistance breeding for YVMV to develop YVMV resistant variety is essential for stable and sustainable okra production.…”
Section: Disease Reaction Of Single Cross Hybrids To Yvmvmentioning
confidence: 99%